2012
DOI: 10.2458/v3i1.16110
|View full text |Cite
|
Sign up to set email alerts
|

Problems in Using Diagnosis in Child and Adolescent Mental Health Services Research

Abstract: This paper presents results from a three-part study on diagnosis of children with affective and behavior disorders. We examined the reliability, discriminant, and predictive validity of common diagnoses used in mental health services research using a research diagnostic interview. Results suggest four problems: a) some diagnoses demonstrate internal consistency only slightly better than symptoms chosen at random; b) diagnosis did not add appreciably to a brief global functioning screen in predicting service us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Other studies have demonstrated that the diagnosis of depression alone is not sufficient for treatment selection; additional information is required (Iniesta et al 2016 ). Moreover, others have shown that diagnostic categories overlap and are not mutually exclusive (Bickman et al 2012c ). In practice, medication is prescribed according to symptoms and not diagnosis (Waszczuk et al 2017 ).…”
Section: Five Problems That Contribute To Poor Servicesmentioning
confidence: 99%
“…Other studies have demonstrated that the diagnosis of depression alone is not sufficient for treatment selection; additional information is required (Iniesta et al 2016 ). Moreover, others have shown that diagnostic categories overlap and are not mutually exclusive (Bickman et al 2012c ). In practice, medication is prescribed according to symptoms and not diagnosis (Waszczuk et al 2017 ).…”
Section: Five Problems That Contribute To Poor Servicesmentioning
confidence: 99%
“…The unreliability of human practice, an issue raised by Kauffman and Sosso and Gallagher, is also particularly important. One issue touched on above is the unreliability of the categories, diagnosis and assessment (Vislie, 2003; Bickman et al, 2012; Frances & Widiger, 2012; BPS – DCP, 2013; Rix, 2015). Another is that for an intervention that emerges from scientific method to be true to itself it cannot propose a hypothesis about an intervention and effectively prove its validity in isolation from the huge range of complexities that exist in moving the intervention into an endlessly variable everyday.…”
Section: Some Immediate Concernsmentioning
confidence: 99%